2018
DOI: 10.1016/j.biortech.2017.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Novel stepwise pH control strategy to improve short chain fatty acid production from sludge anaerobic fermentation

Abstract: This study reports an innovative strategy known as stepwise pH fermentation, developed to enhance the production of short chain volatile fatty acids (SCFA) from waste activated sludge (WAS) anaerobic fermentation. Experimental results confirmed the optimal pH for WAS disruption and acidification was 11 and 9, respectively, and corresponding optimal time was, respectively, 5 d and 2 d. In this scenario, the optimal SCFA yield was 2356 mg chemical oxygen demand (COD)/L, which was much higher than that derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 50 publications
1
15
1
Order By: Relevance
“…Although in R1, the extent of hydrolysis was further augmented on day 25 and exceeded the value observed for R3 (34.1% vs. 28.6%; Fig. 3), the efficiency of solubilised organic substance transformation into SCFAs was higher in the latter reactor (22.1% vs. 18.8%), i.e., the stepwise decrease in pH (pH 11 → pH 9) favoured the augmented conversion of hydrolysed substrates to fermentative SCFAs, in agreement with previous results (Zhao et al 2018b). This phenomenon may be attributable to the inhibitory effect of strongly alkaline conditions on acidogens (Huang et al 2016, Ma et al 2016.…”
Section: Compound Effects Of Fermentation Ph Adjustment On Sludge Hydsupporting
confidence: 92%
See 1 more Smart Citation
“…Although in R1, the extent of hydrolysis was further augmented on day 25 and exceeded the value observed for R3 (34.1% vs. 28.6%; Fig. 3), the efficiency of solubilised organic substance transformation into SCFAs was higher in the latter reactor (22.1% vs. 18.8%), i.e., the stepwise decrease in pH (pH 11 → pH 9) favoured the augmented conversion of hydrolysed substrates to fermentative SCFAs, in agreement with previous results (Zhao et al 2018b). This phenomenon may be attributable to the inhibitory effect of strongly alkaline conditions on acidogens (Huang et al 2016, Ma et al 2016.…”
Section: Compound Effects Of Fermentation Ph Adjustment On Sludge Hydsupporting
confidence: 92%
“…To address this challenge, recent research efforts have focused on dividing the process of anaerobic sludge fermentation into two or more stages so that different pH values can be applied at each stage to maximise chemical hydrolysis at early stages while substantially enhancing biological hydrolysis and acidogenesis at later stages for accumulative SCFA yield (Chen et al 2017, Zhao et al 2018b. However, these works lack a systematic approach and do not provide a clear mechanistic understanding required to increase process synergies and gain a balanced composition of microbial communities for a further enhancement of SCFA production.…”
Section: Introductionmentioning
confidence: 99%
“…pH is a well-known operational parameter which can affect the production of VFA and its composition since it has great influence on hydrolysis and acidogenic fermentation (Atasoy et al 2018; Begum et al 2018; Zhao et al 2018). At the same time, it can also lead to various metabolism pathways to produce different concentrations of individual VFA (Zhou et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations have reported that pH is the most critical parameter that influences the growth rate of microorganisms involved in both acidogenic and hydrolysis processes [60,61]. In another study, the AD process was conducted at the same mesophilic condition, pH 6, HRT (hydraulic retention time) of 5 days, and using a combination with mature compost; the VFA yield from food waste obtained was lower than 20 g VFA-COD/L [18].…”
Section: Discussionmentioning
confidence: 96%